Teachers’ Perception of Principal’s Leadership Style at State Senior High School 2 Muara Sugihan - Ahmadi, Ahmadi; Tiro, Ena Marie (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2025)
The aim of this research is to analyze teachers’ perceptions of the principal’s actions at SMA Negeri 2 Muara Sugihan. The method used was quantitative descriptive research involving 30 teachers as respondents. Data collection was carried out through a questionnaire that assessed perceptions of several leadership styles, such as participative, transformative, and autocratic, as well as teacher motivation and work styles. Research findings show that the majority of teachers have a positive perception of transformational and participative leadership (70% and 65%, respectively), while autocratic leadership has a negative perception (55%). In addition, there is a significant positive correlation between positive perceptions of leadership and greater work motivation (r = 0.65, p < 0.01). This shows the need for more inclusive and inspiring leadership development to increase teachers’ motivation and productivity in schools. It is hoped that this research can help school principals improve leadership effectiveness at SMA Negeri 2 Muara Sugihan.